Differential impact of neutrophil-to-lymphocyte ratio and time-weighted NLR on mortality and survival in critically ill children: insights from a retrospective study - Ma, Dongqing; Wang, Wei; Ma, June; Liu, Wei (Frontiers in Pediatrics, 2025)
BackgroundThe intensive care of critically ill children is challenging due to diverse etiologies and rapid disease progression. Early identification of high-risk patients is crucial for improving outcomes. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential biomarker reflecting the balance between innate and adaptive immune responses, with studies in adults showing its correlation with mortality and survival in intensive care settings. However, its application in pediatric intensive care units (PICU) is less explored.ObjectiveTo examine the impact and predictive value of NLR on in-hospital mortality and 90-day survival rates in critically ill children using data from the Pediatric Intensive Care (PIC) database at the Children's Hospital of Zhejiang University School of Medicine.MethodsThis retrospective cohort study included 3,350 patients from the PIC database, with patients older than 28 days and an ICU stay of at least 48 h. Data on demographic information, ICU admission type, laboratory test results, and clinical outcomes were collected. The normal range of NLR was calculated using the percentile method. Time-weighted NLR was calculated using the trapezoidal rule to estimate the area under the curve of NLR values over time. Statistical analyses included chi-square tests, Mann–Whitney U tests, and multivariable logistic regression to assess the association between NLR and outcomes.ResultsHigher time-weighted NLR levels were significantly associated with increased in-hospital mortality (OR = 1.15, 95% CI: 1.08–1.22, p < 0.001) and shorter ICU length of stay. The Kaplan–Meier survival analysis showed significantly different 90-day survival rates among NLR groups (p = 0.034). Subgroup analysis revealed the highest predictive value of time-weighted NLR in patients under 1 year old with an initial NLR less than 0.48 (AUC = 0.832).ConclusionThe study confirms NLR, particularly in its time-weighted form, as a robust prognostic indicator for critically ill children. Elevated time-weighted NLR levels are associated with increased in-hospital mortality and shorter ICU stays, highlighting its potential for risk stratification and guiding clinical decisions in PICU. The dynamic nature of the time-weighted NLR provides a more accurate reflection of the patient's inflammatory burden over time. However, the retrospective and single-center design of the study limits the generalizability of the results. Future research should address these limitations and explore the integration of NLR with other clinical and laboratory parameters to enhance prognostic accuracy in pediatric critical care settings.